Targeting the PI3K/Akt signaling pathway in gastric carcinoma: A reality for personalized medicine? - Singh, S.; Yap, W.; Arfuso, Frank; Kar, S.; Wang, C.; Cai, W.; Dharmarajan, Arunasalam; Sethi, Gautam; Kumar, Alan Prem (2015)
Frequent activation of phosphatidylinositol-3 kinases (PI3K)/Akt/mTOR signaling pathway in gastric cancer (GC) is gaining immense popularity with identification of mutations and/or amplifications of PIK3CA gene or loss of function of PTEN, a tumor suppressor protein, to name a few; both playing a crucial role in regulating this pathway. These aberrations result in dysregulation of this pathway eventually leading to gastric oncogenesis, hence, there is a need for targeted therapy for more effective anticancer treatment. Several inhibitors are currently in either preclinical or clinical stages for treatment of solid tumors like GC. With so many inhibitors under development, further studies on predictive biomarkers are needed to measure the specificity of any therapeutic intervention. Herein, we review the common dysregulation of PI3K/Akt/mTOR pathway in GC and the various types of single or dual pathway inhibitors under development that might have a superior role in GC treatment. We also summarize the recent developments in identification of predictive biomarkers and propose use of predictive biomarkers to facilitate more personalized cancer therapy with effective PI3K/Akt/mTOR pathway inhibition.